Improved Performance for the Electrochemical Sensing of Acyclovir by Using the rGO–TiO2–Au Nanocomposite-Modified Electrode - Lu, Xin-Yang; Li, Jing; Kong, Fen-Ying; Wei, Mei-Jie; Zhang, Pei; Li, Ying; Fang, Hai-Lin; Wang, Wei (Frontiers in Chemistry, 2022)
An electrochemical sensor for sensitive sensing of acyclovir (ACV) was designed by using the reduced graphene oxide–TiO2–Au nanocomposite-modified glassy carbon electrode (rGO–TiO2–Au/GCE). Transmission electron microscopy, X-ray diffractometer, and X-ray photoelectron spectroscopy were used to confirm morphology, structure, and composition properties of the rGO–TiO2–Au nanocomposites. Cyclic voltammetry and linear sweep voltammetry were used to demonstrate the analytical performance of the rGO–TiO2–Au/GCE for ACV. As a result, rGO–TiO2–Au/GCE exerted the best response for the oxidation of ACV under the pH of 6.0 PB solution, accumulation time of 80 s at open-circuit, and modifier amount of 7 µl. The oxidation peak currents of ACV increased linearly with its concentration in the range of 1–100 µM, and the detection limit was calculated to be 0.3 µM (S/N = 3). The determination of ACV concentrations in tablet samples also demonstrated satisfactory results.